A study of the emotional labor of the professional librarians and the support staff of the University of the Philippines Diliman Library - Cruz, Roscelle C.; Dar Juan, Elijah John F. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2014)
Emotional labor occurs when an employee alters his or her behavior to show appropriate conduct in order to conform to the display rules of an organization required to complete a job. This study focuses on the emotional labor of the librarians and support staff of the University of the Philippines Diliman Library, consisting of the Main Library and the libraries of the 22 degree-granting Units. The study concentrated on the identification of individual factors that impact the emotional labor of the target population. This study was able to determine how the librarians and support staff of UPD Library carry out emotional labor, as well as how they cope with the positive and negative effects of such.
A total of 107 librarians and library support staff who have interaction with clients on a daily work basis were surveyed. This number surpassed the computed target population of 99. Based on the analysis of the gathered data, the following are the principal findings: 1) library and staff of UPDL get enough social support from the supervisors, and 2) feel that they have job autonomy; 3) the library and staff of UPDL have a high positive affinity, 4) low emotional contagion, and 5) carry out emotional labor through genuine and deep acting; 6)the librarians and support staff follow a code of ethics applicable to librarianship; Lastly 7) the librarians and staff of UPDL employ various ways of coping with stressful transactions and rude clients. The most commonly observed coping mechanism is being calm, being relaxed, being cool, and being professional.
It is recommended that the University of the Philippines Diliman library offer training for the librarians and support staff on how to properly shift their emotions. Furthermore, the researcher also suggests that the UPDL consider recruiting people with high positive affinity and high emotional empathy. The researcher also suggests assigning the employees to a variety of jobs and keeping job-rotation to avoid emotional exhaustion. It is also highly suggested that they be given counseling and have the chance to talk to an expert in order to express their thoughts and help them deal with stress appropriately.
As for the future researchers, it is recommended that they conduct studies on the evaluation of patrons and their views on the emotional labor of the professional librarians and support staff of the UPDUL, and the creation of a guideline with display rules on how to deal with clients. It is also suggested that the future researchers conduct survey if any at least a month before finals week so as not to coincide with the heavy workload of the librarians such as a huge volume of clients returning books and other library tasks that need to be accomplished before the closing of the semester.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: University of the Philippines Libraries; Libraries and labor -- Philippines -- Quezon City; Library employees -- Philippines -- Quezon City